Analisa Kinerja Simpang Bersinyal di Kota Jambi - Edwardo, Dimas; Yamali, Fakhrul Rozi (Universitas Batanghari, 2023)
Traffic control at intersections with a high volume of vehicle traffic requires regulation with traffic lights. With the regulation using traffic lights, it is hoped that it can reduce the number of queues experienced by vehicles, compared to those that do not use traffic lights. One of the intersections located in the Jambi City area which is equipped with vehicle traffic control using traffic lights is Hajj Dormitory Intersection. This intersection is a confluence of four arms of the road namely, Jl. H. Agus Salim – Jl. H. Adam Malik – Jl. H. Yunus Sanis – Jl. H. A. Roni Sani, located in the Handil Jaya Village area, Jelutung District, Jambi City. This intersection is a connecting road between regions including; office areas, shops, schools, markets, hospitals, campuses, tourist attractions, settlements, and various other destinations. At these intersections often experience traffic congestion problems, especially during the morning rush hour, afternoon rush hour and evening rush hour. This problem can be seen from the long queue of vehicles that occur. This study aims to analyze the traffic performance of the intersection, as well as obtain the service level of the existing intersection at the intersection of the Hajj Dormitory in Jambi City. The method used in calculating the analysis uses the 2014 Indonesian Road Capacity Guidelines for the capacity of the APILL intersection. The results of the study obtained several conclusions in the form of (1) the performance of the Jambi City Hajj Dormitory intersection, the existing conditions work less than optimally in serving the existing vehicle traffic flow, where the delay value that occurs is greater than 60 seconds/skr for all approaches. For Jl. H. Agus Salim the delay value is 74 seconds/skr and the queue length is 144 meters, Jl. H. Adam Malik delay value of 106 seconds/skr and queue length of 156 meters, Jl. H. Yunus Sanis the delay value is 134 seconds/skr and the queue length is 140 meters, and Jl. H. A. Roni Sani has a delay value of 228 seconds/skr and a queue length of 166 meters. (2) The service level for all approaches is F, where the delay value is greater than 60 seconds/skr. With an average intersection delay value of 116 sec/skr, the level of service F.